Pericytes: Problems and Promises for CNS Repair - Laredo, Fabio; Plebanski, Julia; Tedeschi, Andrea (Frontiers in Cellular Neuroscience, 2019)
Microvascular complications are often associated with slow and progressive damage of various organs. Pericytes are multi-functional mural cells of the microcirculation that control blood flow, vascular permeability and homeostasis. Whereas accumulating evidence suggests that these cells are also implicated in a variety of diseases, pericytes represent promising targets that can be manipulated for therapeutic gain. Here we review the role of pericytes in angiogenesis, blood brain barrier function, neuroinflammation, tissue fibrosis, axon regeneration failure and neurodegeneration. In addition, we outline strategies altering pericyte behavior to point out problems and promises for axon regeneration and central nervous system (CNS) repair following injury or disease.